Model Dinamika Sosio Ekonomi Ibnu Khaldun: Korupsi sebagai Determinan Kemiskinan di Pulau Jawa - Siti Nur Latifah (MONETARIUM: Journal of Economics Business and Management, 2025)
In Islamic history, one of the scholars who discussed the problem of poverty was Ibnu Khaldun. In his analysis, the phenomenon of the rise and fall of a civilization is not only caused by economic variables, but also by a number of non-economic factors. Therefore, in his book entitled "Muqaddimah", he tries to determine interrelated factors such as the role of moral, psychological, political, economic, social and demographic factors. Ibnu Khaldun's explanation shows that poverty is a classic problem and has broad and complex dimensions, so that policy strategies in efforts to eradicate it cannot have one role. Ibn Khaldun's social dynamics model, which is still abstract, is then proxyed into several economic and non-economic variables. Some of these variables are poverty level, Government Expenditures (in the field of social protection), Corruption Crimes, Human Development Index (HDI), Gross Regional Domestic Product (GRDP), Government Investment and Gini Ratio. Sharia parameters are one of the non-economic parameters (moral approach) that are interesting and differentiate between Ibn Khaldun's social dynamics model and the poverty measurement model that has been widely used by researchers. The aim of this research is that with Ibnu Khaldun's dynamic model approach, it is hoped that it will be able to provide solutions in terms of alleviating poverty in various regions, including the island of Java. The data used in this research is panel data, which is a combination of cross-section and time-series data. The panel data in this research uses 6 provinces starting from 2018-2022 using the Panel Data Regression method. The research results show that Government Expenditures (in the field of social protection), Human Development Index (HDI), Gross Regional Domestic Product (GRDP), Government Investment and the Gini Ratio have a significant effect on the number of poor people on the island of Java. Meanwhile, the number of corruption cases has an insignificant effect on the number of poor people on the island of Java.